Words of my perfect teacher : a complete translation of a classic introduction to Tibetan Buddhism - Rinpoche, Patrul; Padmakara Translation Group (New Delhi : SAGE, 1999)
A guide to inner transformation. It introduces the fundamental spiritual practices common to all Tibetan Buddhist traditions.
Includes bibliographical references and index.
Keywords: Rdzogs-chen.; Spiritual life -- Buddhism